Prevalence of Theileria annulata in dairy cattle in Nyala, South Darfur State, Sudan - Abaker, Ismail A. (Vet World, 2017)
AIM: This study was conducted in dairy cattle in Nyala, South Darfur State, during the period from June to September 2015, to study the prevalence of bovine tropical theileriosis. MATERIALS AND METHODS: Apparently, healthy cattle of different age groups, different breeds, and from both sexes were randomly selected from seven locations. Three age groups of cattle were selected, group one <1 year old, group two 1-3 years old, and group three older than 3 years. These cattle were indigenous and cross (Friesian X zebu). A total of 150 blood samples were collected for blood smears, blood in EDTA tubes, and serum samples as well as ticks infesting cattle. Three diagnostic techniques were used such as blood smear, indirect fluorescent antibody test (IFAT), and polymerase chain reaction (PCR). RESULTS: Of 150 samples, 11 (7.3%, 95% confidence interval [CI]: 9.1-5.5) were positive for Theileria spp. piroplasms in the blood smears, 70 (46.7%, 95% CI: 35.7-57.7) were positive for Theileria annulata antibodies in the IFAT, and of 100 samples, 39 (39%, 95% CI: 46.6-31.4) were positive for T. annulata using PCR. The prevalence of T. annulata was higher in indigenous breed than cross cattle by the three diagnostic techniques. The highest prevalence of T. annulata was recorded among cattle older than 3 years old. There were three genera and ten species of ticks found feeding on cattle. These were Rhipicephalus evertsi evertsi, Rhipicephalus decoloratus, Rhipicephalus annulatus, Hyalomma dromedrii, Hyalomma impeltatum, Hyalomma rufipes, Hyalomma anatolicum, Hyalomma truncatum, Amblyomma variegatum, and Amblyomma lepidum. CONCLUSION: The study concluded that tropical theileriosis is prevalent among dairy cattle in Nyala. H. anatolicum was found in very low numbers, suggesting other ticks may play a role in the transmission of the disease. Molecular characterization of T. annulata is recommended for accurate mapping of the disease and evaluates the magnitude problem of tropical theileriosis in South Darfur region.